Continuous glucose monitoring underreports blood glucose during a simulated ultraendurance run in eumenorrheic female runners - Dole, A.; Sims, S.; Gan, H.; Gill, N.; Beaven, M. (International Journal of Sports Physiology and Performance, 2025)
Purpose Continuous-glucose-monitoring (CGM) sensors provide near-real-time glucose data and have been introduced commercially as a tool to inform nutrition decisions. The aim of this pilot study was to explore how factors such as the menstrual phase, extended running duration, and carbohydrates affect CGM outcomes among trained eumenorrheic females in an outdoor simulated ultraendurance running event.